Fertility Behaviour In A Town Of Central Java - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1987)
ABSTRACT Government stimulated family planning in Indonesia started relatively late, in 1969. Especially for overcrowded Java the programme is important to reduce population increase. To understand the reasons for success of the policy it is necessary to have insight in the various factors that determine the acceptance of modern means of birth-control. This study looks into some of these factors in the small town of Banjanegara in Central Java The influence of family income education, government employment and religion are examined, as well as fess easily measurable factors determining fertility behaviour, like social control, opinions in the neigh bourhood and personal experience. The researchers endeavoured to approach these factors as viewed by the local women who practise birth control.